Analytical method development and risk characterisation of anthraquinone in various types of tea. (July 2022) - Yang, Sung-Woong; Yun, Choong-In; Moon, Ji-Young; Lee, Joon-Goo; Kim, Young-Jun
Abstract: Methods available for analysis of natural and artificial anthraquinone contamination of tea are cumbersome due to the need for expensive equipment and purification for sample preparation. Therefore, herein, a new method based on HPLC-PDA, GC/MS, and the QuEChERS method for sample preparation was developed and validated. Comparison of the performance characteristics and measurement uncertainties revealed an LOD of 0.0038 mg/kg, precision of 0.47–2.51%, and measurement uncertainty of 2.5% for GC/MS and an LOD of 0.15 mg/kg, precision of 0.32–3.75%, and measurement uncertainty of 4.9% for HPLC-PDA; thus, GC/MS was concluded to be the more suitable method. Green tea, oolong tea, black tea, and pu-erh tea were analysed by the developed GC/MS method. The hazard quotient values of exposure to anthraquinone from drinking tea indicated that exposure to anthraquinone from drinking tea does not cause adverse health effects in consumers. Highlights: HPLC-PDA, GC/MS method with QuEChERS sampling for anthraquinone analysis in tea. Method validation results indicate GC/MS method is a superior. Hazard quotient values and risk analysis of exposure conducted. Extensive sampling and analysis of commercial teas performed. No adverse health effects were found from current anthraquinone exposure levels.